2003
DOI: 10.1249/01.mss.0000064941.43869.4e
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Telephone and In-Person Interview Versions of the 7-Day PAR

Abstract: The phone and in-person versions of the PAR are equivalent measures for self-reported physical activity. Regardless of age, body mass index, or physical activity level both interview methods had similar estimates for total minutes per week of moderate, hard, and very hard activity. Correlations between each interview method and the TriTrac-R3D were lower for moderate and hard activities as compared with very hard activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 26 publications
5
102
0
1
Order By: Relevance
“…For example, studies of sedentary time and physical activity time have repeatedly reported significant and often strong correlations between self-reported values of time and objectively measured values of time (e.g., Clark et al, 2011;Clemes, David, Zhao, Han, & Brown, 2012;Friedenreich et al, 2006;Hayden-Wade, Coleman, Sallis, & Armstrong, 2003;Strath, Bassett, Ham, & Swartz, 2003). Moreover, analyses of time spent using electronic communication have reported strong correlations (r ϭ .59 to r ϭ .87) between selfreported time spent and actual time spent on Facebook, Twitter, and e-mail (Junco, 2013).…”
Section: Psychometric Properties Of Survey and Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies of sedentary time and physical activity time have repeatedly reported significant and often strong correlations between self-reported values of time and objectively measured values of time (e.g., Clark et al, 2011;Clemes, David, Zhao, Han, & Brown, 2012;Friedenreich et al, 2006;Hayden-Wade, Coleman, Sallis, & Armstrong, 2003;Strath, Bassett, Ham, & Swartz, 2003). Moreover, analyses of time spent using electronic communication have reported strong correlations (r ϭ .59 to r ϭ .87) between selfreported time spent and actual time spent on Facebook, Twitter, and e-mail (Junco, 2013).…”
Section: Psychometric Properties Of Survey and Outcome Measuresmentioning
confidence: 99%
“…Their FL study begins well after this critical period (Pufahl, Rhodes, & Christian, 2000, 2001Rhodes & Pufahl, 2009), and few manage to attain a level of professional working proficiency in an FL during high school. Because various professions from government to business now call for FL skills (Berdan, 2012;Byrne, 2013;Davidson, 2012;Grasgreen, 2013;Helmore, 2013;Skorton & Altschuler, 2012), this often leads to (re-)learning of an FL in adulthood. For this reason, the findings of this study are especially relevant for FL educators in the United States, many of whom are working with adults instead of children.…”
mentioning
confidence: 99%
“…In addition to RPE, a 7-d physical activity recall (7-d PAR) interview took place at the end of the supplementation period. The purpose of the 7-d PAR, a reliable index in assessing activity levels 26 was to explore the activity levels of the two groups toward the end of the experimental period.…”
Section: Ratings Of Perceived Exertion and 7-d Physical Activity Recallmentioning
confidence: 99%
“…The second categorization was weight status using BMI defined as normal weight (BMI < 25), overweight (BMI 25-29.9), or obese (BMI ≥ 30). Third, based on accelerometer MVPA, participants were categorized as meeting or not meeting the public health recommendations for MVPA (Haskell et al, 2007) if they engaged in an average of 30 minutes or more of MVPA per day (Hayden-Wade et al, 2003). Finally, participants were grouped into non-Hispanic white and "other" categories of ethnicity; the sample sizes within ethnic groups were not large enough to analyze data separately for each category.…”
Section: Analysesmentioning
confidence: 99%